The Parenting Styles on Handwashing Behavior for Preventing Coronavirus Disease 19 Spread on Children with Mental Retardation - Esme Anggeriyane; Ruslinawati Ruslinawati; Regina Wafa Azkiya (Universitas Muhammadiyah Surakarta, 2023)
The increasing number of Coronavirus Disease 19 (Covid 19) in Indonesia has made the government implement health protocols, one of which is washing hands. Children with mental retardation who have intellectual abilities below the average and have difficulty implementing it. The parenting style applied to children will affect the child's behavior, one of which is handwashing behavior. This study aimed to determine the relationship of parenting on handwashing behavior for spread preventing Coronavirus Disease 19 in children with mental retardation. This study utilized a quantitative correlation with a cross-sectional approach. A total of 33 parents who have children with mild mental retardation in Special School 2 Banjarmasin. The research instrument is the parenting style questionnaire and the handwashing behavior observation sheet. The results showed from 33 parents who applied democratic parenting were 21 people (63%), as many as 19 children (57%) with good handwashing behavior. Chi-Square test obtained p-value = 0.000 < ?= 0.05. There is the relationship between parenting on handwashing behavior for Preventing Coronavirus Disease 19 Spread on Children with Mental Retardation. The right parenting pattern for children with mental retardation can help children grow and develop properly.